Corporate leverage and financial decision in the Indian textile industry - Azhagaiah, Ramachandran (Managing global transitions, 2012)
In the presence of market imperfections, leverage has the potential to have an important influence on investment decisions. If a firm makes money on its borrowing (has favorable financial leverage), the shareholders realize higher earnings per share (eps) than would be the case in the absence of debt, as the debt-equity ratio (der) is a long term risk measure. In the present study 25 textile firms, which are listed in Bombay Stock Exchange are taken as a sample for the study period from 2004 to 2008. The study reveals that the firms i. e. acm, afl, asl, basml, bcil, gsm, gdpm and gjml show significant growth rate in financial, operating and combined leverage.
Keywords: capital structure; corporate leverage; debt equitz ratio; financial decisions; financial leverage; finančne odločitve; finančni vzvodi; India; Indija; kapitalska struktura; kazalnik finančnega vzvoda; operating leverage; podjetja; poslovni vzvodi; tekstilna industrija